Perbedaan Pengaruh Pemberian Insulin dan Ekstrak Zingiber officinale Terhadap Berat Badan Lahir Anak Rattus Norvegicus Model Diabetes Melitus Pragestasional - Ratih Mega Septiasari (Universitas Muhammadiyah Surabaya, 2018)
Diabetes during pregnancy can be divided into pregestational diabetes and gestational diabetes. The risk of fetal Diabetes Mellitus pregestational (DMpG) patients can be either macrosomia or low birth weight. The purpose of this study was to investigate the differences in the administration effect of insulin and Zingiber officinale extract on birth weight of Rattus norvegicus pregestational diabetes mellitus model. This research is an experimental research using post test only control group design. Samples contained 30 pregnant Rattus norvegicus and divided into 5 groups, where K0 (negative control group) and K1 (positive control group) given aquadest 1cc, K2 given insulin 1IU, K3 given ginger extract 500mg/ kg BW, K4 given insulin 1IU and ginger extract 500mg/ kg BW. Treatment was administered during the first 16 days of pregnancy. On the 17th day, the rats were terminated and then the birth weight was measured with the scale. Data analysis using One-way ANOVA test followed by Tamhane test. The results showed that there was a difference of birth weight in the insulin treatment group and ginger extract treatment group (p-value = 0,037 < α =0,05). The conclusion of this study was Zingiber officinale can be used as a single therapy or combination with insulin of Rattus norvegicus pregestational diabetes mellitus model.